2014
DOI: 10.1063/1.4869738
|View full text |Cite
|
Sign up to set email alerts
|

On the redox origin of surface trapping in AlGaN/GaN high electron mobility transistors

Abstract: Water-related redox couples in ambient air are identified as an important source of the surface trapping states, dynamic on-resistance, and drain current collapse in AlGaN/GaN high electron mobility transistors (HEMTs). Through in-situ X-ray photoelectron spectroscopy (XPS), direct signature of the water-related species—hydroxyl groups (OH) was found at the AlGaN surface at room temperature. It was also found that these species, as well as the current collapse, can be thermally removed above 200 °C in vacuum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Hence, these results confirm that the moisture plays a critical role in the degradation of the characteristics of conventional GaN-based MIS-HEMT devices, in agreement with recent reports indicating that the moisture on the AlGaN surface can modify significantly the 2DEG [11], [20]. Moreover, Gao et al showed that this adverse effects are also present even with a 20-nm-thick SiN passivation layer, but it can be mitigated with a thicker SiN layer (200 nm) [11].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Hence, these results confirm that the moisture plays a critical role in the degradation of the characteristics of conventional GaN-based MIS-HEMT devices, in agreement with recent reports indicating that the moisture on the AlGaN surface can modify significantly the 2DEG [11], [20]. Moreover, Gao et al showed that this adverse effects are also present even with a 20-nm-thick SiN passivation layer, but it can be mitigated with a thicker SiN layer (200 nm) [11].…”
Section: Resultssupporting
confidence: 92%
“…Hence, these results confirm that the moisture plays a critical role in the degradation of the characteristics of conventional GaN-based MIS-HEMT devices, in agreement with recent reports indicating that the moisture on the AlGaN surface can modify significantly the 2DEG [11], [20]. Moreover, Gao et al showed that this adverse effects are also present even with a 20-nm-thick SiN passivation layer, but it can be mitigated with a thicker SiN layer (200 nm) [11]. In the present case, the passivation layer is 100 nm thick, and according to the results it seems not to be thick enough to impede either the water permeation through the SiN layer and reaching the AlGaN surface [17], or the electrons from the gate in reverse bias being injected onto the passivation surface, as Gao et al suggested [11].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…For AlGaN / GaN high-electron-mobility transistors (HEMTs) under ambient moisture, Gao et al found current collapse by the ionization and deionization of water molecules at the device surface [21,22].…”
mentioning
confidence: 99%
“…The generated holes drift in opposite direction toward the crystal surface where the negative surface charge is lowered. The accumulation of positive charges at the surface changes the configuration of adsorbates , predominantly consisting of chemically bound oxide or hydroxide and physically bound water . The ratios between chemically bound species as well as the pH value of the adsorbed water layer will adjust to the more positive charge at the semiconductor surface .…”
Section: Resultsmentioning
confidence: 99%